Elevated ductility, optical, and air barrier properties of poly (butyleneadipate‐co‐terephthalate) bio‐based films via novel thermoplastic starch feature. (21st December 2018) - Zhang, Shuidong; Lin, Zesheng; Li, Jun; Jiang, Guo; Hu, Changying
Abstract : It is important to develop high performances biodegradable polymers to eliminate the "white pollution" evoked by petroleum‐based polymer. Thermoplastic starch (TPS) with nano‐ellipse configuration was fabricated to reinforce the performances of poly (butylene adipate co‐terephthalate) (PBAT) biocomposites. Effects of tartaric acid (TA) (0.5% wt) on the structure of TPS and compatibility for PBAT were evaluated by Fourier‐transform infrared spectroscopy (FTIR), viscosity and rheological measurement, dynamic mechanical analysis (DMA) and scanning electron microscope (SEM), respectively. They revealed that TA reduced the molecular weight of starch and shear viscosity of TPS were beneficial for TPS dispersing in PBAT matrix with 184‐nm averaged diameter. PBAT/TPS‐TA (70:30 wt%) biocomposite films were blew with different blow‐up ratio. The morphology of films presented that nano‐TPS‐TA wrapped in the PBAT matrix and deformed from ball to capsule feature without agglomeration. Compared with those of PBAT film, the increment in elongation at break of PBAT/TPS‐TA film was 100%. The air permeability and UV‐VIS transmittance of PBAT/TPS‐TA films decreased from 6.92 × 10 −9 to 3.72 × 10 −9  cm 3 ·cm·cm −2  s −1  Pa −1 and 47.6% to 23.5%, respectively. This study proposed a facile approach to fabricate low‐cost PBAT films with significant improved mechanical, optical, and air barrier properties for commercial application. Mechanism for nanoparticles of TPS‐TA motivated the elevated performances was proposed, synchronously.